Markers of cardiovascular complications in patients with type 2 diabetes mellitus and arterial hypertension (Bangladesh Journal of Medical Science, 2018)
Background: Hypertensive patients with type 2 diabetes mellitus are also at increased risk for diabetes mellitus–specific complications, including nephropathy. Even the smallest degree of albuminuria increases risk for cardiovascular diseases and all-cause death. The common conditions coexisting with type 2 diabetes (e.g., hypertension and dyslipidemia) are clear risk factors for cardiovascular diseases.Methods and materials: The first (I) group consists of 99 obtained patients with type 2 and AH, the second (II) includes 49 practically healthy people. We evaluated such markers of cardiovascular complications as glycated hemoglobin, lipid profile components by biochemical method and albumin excretion rate with the help of enzyme immunoassay.Result: The positive correlation between the level of albumin excretion rate and glycated hemoglobin (r = 0,23, p < 0,001) is confirmed that albuminuria is a main marker of diabetic nephropathy. The positive correlation between albuminuria and low density lipoproteins (r = 0,34, p < 0,001), triglycerides (r = 0,04, p < 0,001) is the definition of the important role of dyslipidemia in diabetic nephropathy.Conclusion: Determination of albumin excretion rate, glycated hemoglobin as markers of nephropathy, lipid profile components is necessary for patients with type 2 diabetes mellitus and arterial hypertension for prevention cardiovascular complications.Bangladesh Journal of Medical Science Vol.17(2) 2018 p.319-322